2018
DOI: 10.1111/gtc.12586
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of cyclic‐di‐GMP by a riboswitch conducts translational repression through masking the ribosome‐binding site distant from the aptamer domain

Abstract: The riboswitch is a class of RNA-based gene regulatory machinery that is dependent on recognition of its target ligand by RNA tertiary structures. Ligand recognition is achieved by the aptamer domain, and ligand-dependent structural changes of the expression platform then usually mediate termination of transcription or translational initiation. Ligand-dependent structural changes of the aptamer domain and expression platform have been reported for several riboswitches with short (<40 nucleotides) expression pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…Levels of c-di-GMP are elevated in biofilms, thus it is possible that TfoY may aid in dispersal from biofilms by enhancing motility. Conversely, we did not observe TfoY to significantly influence motility when c-di-GMP levels were low, which is consistent with a prior analysis that analyzed TfoY-dependent [24,26,28]. In contrast, transcripts produced from promoters P3 and P4 (red bent arrows), driven by the c-di-GMP binding transcriptional activator VpsR, do not contain the Vc2 riboswitch [26].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Levels of c-di-GMP are elevated in biofilms, thus it is possible that TfoY may aid in dispersal from biofilms by enhancing motility. Conversely, we did not observe TfoY to significantly influence motility when c-di-GMP levels were low, which is consistent with a prior analysis that analyzed TfoY-dependent [24,26,28]. In contrast, transcripts produced from promoters P3 and P4 (red bent arrows), driven by the c-di-GMP binding transcriptional activator VpsR, do not contain the Vc2 riboswitch [26].…”
Section: Discussionsupporting
confidence: 90%
“…Notably, levels of TfoY were significantly enriched in the low c-di-GMP strain in the absence of lonA . It was previously shown that c-di-GMP limits production of TfoY protein by binding to a riboswitch (Vc2) located in the 5’UTR of tfoY mRNA [ 24 , 27 , 28 ]. Thus, this result is consistent with prior analyses, which have shown that decreasing levels of c-di-GMP results in enhanced TfoY translation, and suggests that LonA plays a more significant role in regulating levels of TfoY when c-di-GMP levels are low [ 24 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations